2000
DOI: 10.3727/036012900816356181
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Low-Intensity Millimeter-Wave Electro-Magnetic Stimulation of Acupuncture Points

Abstract: The aim of this study was to investigate the effects of the millimeter-wave bioresonance therapy on acute inflammation and stressful conditions in experimental models. Licking reaction in mice as a component of the hypersensitive state evoked by subcutaneous formalin (0.03 ml of 1% solution) injection into the right hind paw was monitored. Different parameters of electro-magnetic stimulation (frequencies 43 GHz and 61 GHz, intensities from 0.1 to 7 mW/cm2, the exposure time for 3 min. or 10 min.) applied to ip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Taking into account local energy absorption, the most intriguing question is the link of observed effects with the exposure site. Hypoalgesic effects were found in animals and humans exposed at the acupuncture points [5860]. Moreover, it was found that the most pronounced results were obtained by exposing the skin areas with the high nerve endings concentration [61] confirming the role of the peripheral neural system.…”
Section: Biological Effects Of Millimeter Wavesmentioning
confidence: 99%
“…Taking into account local energy absorption, the most intriguing question is the link of observed effects with the exposure site. Hypoalgesic effects were found in animals and humans exposed at the acupuncture points [5860]. Moreover, it was found that the most pronounced results were obtained by exposing the skin areas with the high nerve endings concentration [61] confirming the role of the peripheral neural system.…”
Section: Biological Effects Of Millimeter Wavesmentioning
confidence: 99%
“…On the other hand, it has been suggested that at least some beneficial clinical effects can be due to induced magnetic and electrostatic forces. [7][8][9][10] This is an area that needs further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…A growing number of studies proposes various types of non‐pharmacologic treatments for the improvement of some psychophysical stress‐related symptoms. Some are based on mental‐type techniques (Hawley, Ringo Ho, Zuroff, & Blatt, 2007; Lindauer, et al, 2008; Pagani, et al, 2007; Woller, Hartkamp, & Tress, 2007), on physical exercise (Esch, Duckstein, Welke, & Braun, 2007; Goon, et al, 2009; Granath, Ingvarsson, von Thiele, & Lundberg, 2006; Lee, et al, 2007; Porter, 2002; Satyapriya, Nagendra, Nagarathna, & Padmalatha, 2009; Smith, Hancock, Blake‐Mortimer, & Eckert, 2007; Wall, 2005, 2008; Yoga for Anxiety and Depression, 2009), massages (Back, Tam, Lee, & Haraldsson, 2009; Billhult, Lindholm, Gunnarsson, & Stener‐Victorin, 2009; Garner, et al, 2008; Hernandez‐Reif, Diego, & Field, 2007; Jeong, et al, 2008; Moraska, Pollini, Boulanger, Brooks, & Teitlebaum, 2008; Sharpe, Williams, Granner, & Hussey, 2007), physical stimulation on acupuncture points or body areas (Atkins & Harris, 2008; Fassoulaki, Paraskeva, Patris, Pourgiezi, & Kostopanagiotou, 2003; Hollifield, Sinclair‐Lian, Warner, & Hammerschlag, 2007; Huang, et al, 2005; Kim, et al, 2009; Middlekauff, et al, 2002; Middlekauff, Yu, & Hui, 2001; Ogata, Sugenoya, Nishimura, & Matsumoto, 2005; Pease, Sollom, & Wayne, 2009), and even with a different apparatus (Lysenyuk, Samosyuk, Kulikovich, & Kozhanova, 2000; Tsimmerman Ia, Kochurova, & Vladimirskii, 2006; Usichenko & Herget, 2003; Usichenko, Ivashkivsky, & Gizhko, 2003). The aim of this work is to evaluate by means of psychometric tests the effectiveness of psychophysical stress‐related symptoms of a treatment of stimulation on some reflex therapy points in the auricle by using a radio‐electric asymmetric conveyer (REAC) (Rinaldi, 2001).…”
Section: Introductionmentioning
confidence: 99%